2010
DOI: 10.1111/j.1538-7836.2009.03666.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial thrombosis: relevance of a model with two levels of severity assessed by histologic, ultrastructural and functional characterization

Abstract: thrombosis: relevance of a model with two levels of severity assessed by histologic, ultrastructural and functional characterization. J Thromb Haemost 2010; 8: 173-84.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 36 publications
(70 reference statements)
8
82
1
Order By: Relevance
“…Therefore, this treatment is considered a reasonable model of thrombosis (43,44). Although other models often damage endothelial cells but do not cause them to detach from the vessel wall to expose collagen, recent studies, published after these studies were completed, from Hechler et al (45) have demonstrated that it is possible to denude the endothelium by laser injury if properly applied. In WT mice, we found that the time to occlusion time is 6.1 Ϯ 2.2 min, which is reasonably consistent with other data (46).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this treatment is considered a reasonable model of thrombosis (43,44). Although other models often damage endothelial cells but do not cause them to detach from the vessel wall to expose collagen, recent studies, published after these studies were completed, from Hechler et al (45) have demonstrated that it is possible to denude the endothelium by laser injury if properly applied. In WT mice, we found that the time to occlusion time is 6.1 Ϯ 2.2 min, which is reasonably consistent with other data (46).…”
Section: Discussionmentioning
confidence: 99%
“…10 To be active fully, Akt requires phosphorylation on Thr 308 by PDK1 21 and Ser 9 in GSK3a and b, respectively) by Akt following platelet stimulation. GSK3b, the most abundant isoform, 40 has been shown to regulate negatively platelet functions 22 possibly by downregulating a IIb b 3 outside-in signaling, at least in vitro under ADP stimulation. 33 Here we show that pharmacologic inhibition of GSK3 rescues thrombus stabilization of PI3Kb-null platelet or AZD6482-treated human platelets under high shear rate.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the role of platelet PI3Kb in arterial thrombus stability in vivo, we performed a laser beam-induced local deep lesion of mesenteric arterioles 22 and monitored platelet thrombus formation by intravital microscopy. WT platelets formed a thrombus at the site of injury (supplemental Video 3; Figure 4A) that was either massive (thrombus size .28 000 mm 2 ) in 51.5% of the cases, strongly reducing the lumen of the vessel, or smaller (thrombus size ,28 000 mm 2 ) in 48.5% of the cases.…”
Section: Detachment Of Platelet Emboli From the Thrombus Formed On Dementioning
confidence: 99%
“…As previously shown, laser-induced thrombosis in the cremaster microcirculation represents a model of localized, thrombin-driven thrombosis. 27,28 When subjected to this model, CalDAG-GEFI Ϫ/Ϫ mice showed decreased platelet accumulation compared with WT mice in both arterioles (Figure 2A-B) and to a lesser extent in venules ( Figure 2D-E). Thrombi in venules of CalDAG-GEFI Ϫ/Ϫ mice grew slowly but remained stably anchored to the vessel wall.…”
Section: Thrombotic Profile Of Caldag-gefi ؊/؊ and Clopidogrel-treatementioning
confidence: 99%